Self-Actualization of The Main Character Gadis: a Case Study at Liye’s Novel Sesuk - Disza Aulia Haryanto; Somadi Sosrohadi; Sukirno (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
A literary work is seen not only as a work of art that is expressed through various experiences in social life, but also as a creative work related to psychological symptoms, namely human attitudes and behavior. The purpose of this study is to describe the characteristics of the main character, to describe the form of fulfillment of needs as the main character's self-actualization process, and to describe the self-actualization characteristics contained in the main character. This study uses Abraham Maslow's theory of humanistic psychology. The research method used is descriptive qualitative method. The data were obtained from the text in the novel Sesuk by Tere Liye, data from literature studies using heuristic reading techniques. Data analysis was performed by using hermeneutic reading techniques. The results of the study show that Gadis as the main character has both good and bad characters. Fulfilling the physiological needs of the female character, namely eating, drinking, and resting. The fulfillment of the need for security is shown by other characters who look after the girl so that she feels safe. The need for love and belonging is demonstrated by the girl character getting love from the people around her. The need for self-esteem and appreciation is shown by those who try to maintain their self-esteem and parents and people around them who give awards in the form of appreciation to them. The need for actualization is shown through the return of the girl's family to become a complete and harmonious family.